Short-range plasmonic nanofocusing within submicron regimes facilitates in situ probing and promoting of interfacial reactions. Issue 6 (26th January 2016) - Yu, Chen-Chieh; Lin, Keng-Te; Su, Pao-Yun; Wang, En-Yun; Yen, Yu-Ting; Chen, Hsuen-Li
Abstract : The plasmonic nanofocusing configuration facilitates in situ probing and promoting of interfacial reactions on the dielectric NPs simultaneously. Abstract : In this study, a simple configuration, based on high-index dielectric nanoparticles (NPs) and plasmonic nanostructures, is employed for the nanofocusing of submicron-short-range surface plasmon polaritons (SPPs). The excited SPPs are locally bound and focused at the interface between the dielectric NPs and the underlying metallic nanostructures, thereby greatly enhancing the local electromagnetic field. Taking advantage of the surface properties of the dielectric NPs, this system performs various functions. For example, the nanofocusing of submicron-short-range SPPs is used to enhance the Raman signals of gas molecules adsorbed on the dielectric NPs. In addition, the presence of the local strong electromagnetic field accelerates the rates of interfacial reactions on the surfaces of the dielectric NPs. Therefore, the proposed nanofocusing configuration can both promote and probe interfacial reactions simultaneously. Herein, the promotion and probing of the desorption of EtOH vapor are described, as well as the photodegradation of methylene blue. Moreover, the nanofocusing of SPPs is demonstrated on an aluminum surface in both the visible and UV regimes, a process that has not been achieved using conventional tapered waveguide nanofocusing structures. Therefore, the nanofocusing of submicron-short-range SPPs by dielectric NPs on plasmonic nanostructures is not limited to low-loss noble metals. Accordingly, this system has potential for use in light management and on-chip green devices and sensors.